2018
DOI: 10.3762/bjnano.9.170
|View full text |Cite
|
Sign up to set email alerts
|

A visible-light-controlled platform for prolonged drug release based on Ag-doped TiO2 nanotubes with a hydrophobic layer

Abstract: In this work, a visible-light-controlled drug release platform was constructed for localized and prolonged drug release based on two-layer titania nanotubes (TNTs) fabricated using by an in situ voltage up-anodization process. The visible-light photocatalytic activity is improved by loading Ag onto the TNTs by NaBH4 reduction. Then, the TNTs containing Ag nanoparticles were modified with dodecanethiol (NDM) to create a hydrophobic layer. To demonstrate the visible-light-controlled drug release, the Zn2+ releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This effect can be related to the increase of nanotubes diameter from 35–45 nm up to 100–120 nm, and thus a higher ability to penetrate the interior of the nanotubes by the liquid. The increase of hydrophobicity of TNT layers (diameter 33 nm) after their decoration by AgNPs (diameter 35 nm) was also noticed by Caihong et al [33]. The insertion of an AgNPs-enriched implant into an aqueous solution is associated with the oxidation of metal nanoparticles and the releasing of silver ions, which has direct impact on potential antimicrobial properties of the produced coatings [34].…”
Section: Discussionmentioning
confidence: 82%
“…This effect can be related to the increase of nanotubes diameter from 35–45 nm up to 100–120 nm, and thus a higher ability to penetrate the interior of the nanotubes by the liquid. The increase of hydrophobicity of TNT layers (diameter 33 nm) after their decoration by AgNPs (diameter 35 nm) was also noticed by Caihong et al [33]. The insertion of an AgNPs-enriched implant into an aqueous solution is associated with the oxidation of metal nanoparticles and the releasing of silver ions, which has direct impact on potential antimicrobial properties of the produced coatings [34].…”
Section: Discussionmentioning
confidence: 82%
“…As mentioned above, TiO 2 nanotubes as drug delivery system would lead to initial burst release; several techniques have been developed to prolong drug release from TNT, such as changed wettability of TiO 2 nanotubes surface to control the release rate for the hydrophobic drug [37,38], constructed polymer coatings to close the pore of nanotubes [21,[39][40][41], and stimulated drug release by external factors [42][43][44][45]. Based on these previous researches, we hypothesized the electrochemical deposition of polymer layers could effectively reduce burst release and extend drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of research, it was found that the wettability could be changed by external stimuli [7]. Due to their unique properties, stimuli-responsive surfaces with switchable wettability have great potential in many technological applications, including smart textiles [8], drug delivery [9], and smart separation [10]. Up to now, various external stimuli, such as light illumination [11], electric feld [12], pH value [13], ion exchange [14], and heating [15] have been used to change the wettability of surfaces.…”
Section: Introductionmentioning
confidence: 99%